A= -81 + square root of 113
a<span>≈</span> -70.36985418
Answer:
5
Step-by-step explanation:
f(-4)= -2(-4)-3
=8-3
=5
Answer:
-39991'
Step-by-step explanation:
We require the sum of 7 terms of the G.S. -1, 6, -36 .....
The common ratio r = 6/-1 = -6 and the first term = -1.
Sum of n terms = a1 . (r^n - 1) / (r - 1)
Sum of 7 terms = -1 * (-6)^7 - 1) / (-6 - 1)
= -1 * 39991
= -39991 (answer).
Answer:
16 inches after one year
Step-by-step explanation:
in 3/4 a year tree grew 12 inches
divide by 3
multiply by 4
16 inches
Y=24x+48
24 per hour (x) plus the 48 she already made would equal a total (y).